2016
DOI: 10.2147/copd.s101612
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of clinically important deteriorations in COPD with umeclidinium/vilanterol

Abstract: BackgroundMinimizing the risk of disease progression and exacerbations is the key goal of COPD management, as these are well-established indicators of poor COPD prognosis. We developed a novel composite end point assessing three important aspects (lung function, health status, and exacerbations) of worsening in COPD. The objective was to determine whether dual bronchodilation with umeclidinium/vilanterol (UMEC/VI) reduces clinically important deteriorations (CIDs) in COPD versus placebo or bronchodilator monot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
117
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(123 citation statements)
references
References 26 publications
4
117
0
2
Order By: Relevance
“…The current study focused on patients from three similar studies with a large proportion of symptomatic COPD patients (all mMRC ≥2), 55% and 45% of the ITT and MN subgroups, respectively, presenting with severe lung function impairment at baseline. The current findings are commensurate with the earlier study by Singh and colleagues [15], highlighting that reducing the risk of a first CID is as likely in low and high risk patients and when using dual bronchodilators as first- or second-line therapy. It is therefore important that the early use of dual therapy was compared with monotherapy in this MN population.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The current study focused on patients from three similar studies with a large proportion of symptomatic COPD patients (all mMRC ≥2), 55% and 45% of the ITT and MN subgroups, respectively, presenting with severe lung function impairment at baseline. The current findings are commensurate with the earlier study by Singh and colleagues [15], highlighting that reducing the risk of a first CID is as likely in low and high risk patients and when using dual bronchodilators as first- or second-line therapy. It is therefore important that the early use of dual therapy was compared with monotherapy in this MN population.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study has demonstrated the dual bronchodilator therapy may reduce the risk of short-term CID and potentially provide greater airway stability compared with monotherapy [15]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, LAMA/LABA bronchodilation appear to be similarly beneficial compared with LAMA monotherapy in symptomatic patients who have or have not previously received a COPD maintenance treatment, which questions the rationale for a delayed stepwise approach in managing persistent symptoms [16,17]. There is also evidence that early use of LAMA/LABA combinations may improve disease stability compared with LAMA monotherapy by protecting symptomatic patients, including maintenance-naïve (MN) patients, from further disease deterioration [16,[18][19][20]. Dual therapy could therefore provide the opportunity for maximal bronchodilation, with a view to minimizing daily symptoms, improving quality of life (QoL), and preventing further disease deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…Group B patients should be started on single bronchodilator, either LAMA or LABA, while the LAMA/LABA combination may be started soon in the more symptomatic patients. Accordingly, a recent exploratory analysis, showed that the LAMA/LABA combination was superior to placebo and monotherapy in symptomatic patients with low exacerbation risk [42]. ICS in not recommended alone nor as an addition to either LAMA or LABA in group B.…”
Section: Disease Managementmentioning
confidence: 99%